Kondisi Terumbu Karang Di Perairan Pesisir Desa Amahusu (Batu Capeu) Kota Ambon - Ronald Darlly Hukubun (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
Coral reefs are the most productive and diverse ecosystems. This study aims to determine the condition of coral reefs, using the Line Intercept Transect (LIT) method. Data were collected in October 2018. The results of the study found 18 categories of benthic growth forms crossed by the transect line, where the biotic component was 63.02% and the abiotic component was 36.98%. The biotic component consists of 26.6% hard corals, 0.44% dead corals, 3.54% algae, and 32.44% other fauna while the abiotic component is only dominated by 36.98% sand. Coral cover of 26.6% shows the condition of coral reefs is in a fair condition. The cause of the low percentage of coral cover caused by human activity (anthropogenic impact).Keywords: Coral reef; Line Intercept Transect; Amahusu Village